Annual Plan (2000-2001) Detailed Proposals Volume II Haryana State - Planning Commission (Planning Commission, 2000)
THE W.R.C.P. was necessitated to achieve the objectives of managing the total available water resources of the State efficiently and economically keeping in view the demand of the water users, ensuring equitable distribution of water amongst beneficiaries by rehabilitating the existing canal & drainage works in the State for self sustaining the department. With these objectives the studies were carried out in co-ordination /consultation with World Bank before finalization of the W.R.C.P. costing Rs. 1858.25 Crore for H.I.D. & HSMITC ( Rs. 711.00 Crore for works & Rs.637.00 Crore for Estt. Upto 9/99) = Rs. 1348.00 Crores.)
Planning Department Government of Haryana
Planning Department Government of Haryana
Keywords: Minor Irrigation and Tubewells Corporation (MITC); Command Area Development Authority(CADA); Power; Non Conventional Energy Sources Industries; Mines & Geology; Electronics; Weights & Measures (Food and Supplies); Civil Aviation; PWD(B&R); Road Transport; Science & Technology; Environmental Programmes; Secretariat Economic Services; Census Survey & Statistics; Tourism; Decentralised Planning